(3GdJLGQI GdEdcJQhfjI hegGQGJ GdJShjb GdYdejs - (3GdSjO(B, (3YdjhIs ((3GdbGgQI(B:s (3OGQ GdCejf(B,s, 2002)
(3GdJLGQI GdEdcJQhfjI,egGQGJ GdJShjb GdYdej,Gdeaghe GdJShjbj GdMOjK hGdHjFI GdJShjbjI,HMhK GdJShjb,GSJQGJjLjI GdJQhjL hSdhc GdeSJgdcs
(3HHdhZQGajG U(B.260s
Keywords: (3GdJLGQIs; (3GdJShjbs; (3GdeSJgdchfs